Historical dictionary of the Gambia - Perfect, David, 1960- (Historical dictionaries of Africa., 2016)
"Contains a chronology, an introduction, an extensive bibliograpy, and more than 700 cross-referenced entries on important topics, including personalities, politics, economy, foreign relations, religion, and culture. This book is an excellent resource for students, researchers, and anyone wanting to know more about The Gambia."--Page 4 of cover